SAT0209 The Risk for Initial Digital Ulcer Involvement in SSC Patients Decreases with Disease Duration Since the Beginning of Raynaud Phenomenon. (23rd January 2014) - Moinzadeh, P.; Hunzelmann, N.; Mueller-Ladner, U.; Meier, F.; Riemekasten, G.; Becker, M.; Kreuter, A.; Wozel, G.; Melchers, I.; Sardy, M.; Herrgott, I.; Graefenstein, K.; et al.
Abstract : Background: Digital ulcers (DU) constitute an important component of disease burden in SSc. Among patients with SSc it has been reported that 15 to 25 % have active digital ulcers and 35 % have or have had DUs in the past. The natural history, including risk as well as protective factors for the development of DU are only partially understood. Objectives: To identify new clinical parameters as risk factors for the development of DU. Methods: In a prospective study, patients with definite SSc were included in three groups: i) group 1 for patients with active DU; ii) group 2 for patients, who have no active DU at baseline, but had reliably documented SSc-related DU in the past; iii) group 3 for patients, who neither have active DU at inclusion nor had DU in their past. Patients in group 3 are followed on months 6, 12, 24 for the development of DU. Results: 87 patients were included in group 1, 148 patients in group 2. 420 patients were recruited for group 3. Mean disease duration at enrolment as determined by first non-Raynaud organ involvement was 10.6 years in group 1, 2 and 8.8 in group 3. Patients in group 3 with no history of DU were significantly (p< 0.001) older (median 60 years vs. 55 years in group 1, 2), had lower mRSS (median 6 vs. 9), a lower frequency of lung fibrosis (38.4% vs. 54.2%) and a lower frequency of Scl-70 autoantibody (18.5% vs 40.9%). In group 3 after a mean follow up of 1.6 years, only 17/420 (4.0%) patients developed a DU, with decreasing frequency over the observation time. The risk to develop DU was highest within 3 years after beginning of raynaud phenomenon (RP). Risk for DU was significantly reduced for patients within 3-6 years after beginning of RP (OR=0, 114 95%>KI (0, 014;0, 952)) and >6 years ((OR = 0, 337, 95%>KI (0, 121;0, 943)). Conclusions: In addition to well known risk factors for DU, including diffuse disease, high mRSS, Scl-70 antibody, this study indicates that a) a substantial number of SSc patients do not develop DU and b) disease duration is inversely correlated with the risk to develop DU for the first time. Disclosure of Interest: P. Moinzadeh Grant/research support from: This study was financially supported by Actelion Pharmaceuticals Germany., N. Hunzelmann Grant/research support from: This study was financially supported by Actelion Pharmaceuticals Germany., U. Mueller-Ladner Grant/research support from: This study was financially supported by Actelion Pharmaceuticals Germany., F. Meier Grant/research support from: This study was financially supported by Actelion Pharmaceuticals Germany., G. Riemekasten Grant/research support from: This study was financially supported by Actelion Pharmaceuticals Germany., M. Becker Grant/research support from: This study was financially supported by Actelion Pharmaceuticals Germany., A. Kreuter Grant/research support from: This study was financially supported by Actelion Pharmaceuticals Germany., G. Wozel Grant/research support from: This study was financially supported by Actelion Pharmaceuticals Germany., I. Melchers Grant/research support from: This study was financially supported by Actelion Pharmaceuticals Germany., M. Sardy Grant/research support from: This study was financially supported by Actelion Pharmaceuticals Germany., I. Herrgott Grant/research support from: This study was financially supported by Actelion Pharmaceuticals Germany., K. Graefenstein Grant/research support from: This study was financially supported by Actelion Pharmaceuticals Germany., G. Fierlbeck Grant/research support from: This study was financially supported by Actelion Pharmaceuticals Germany., C. Pfeiffer Grant/research support from: This study was financially supported by Actelion Pharmaceuticals Germany., M. Worm Grant/research support from: This study was financially supported by Actelion Pharmaceuticals Germany., H. Burkhardt Grant/research support from: This study was financially supported by Actelion Pharmaceuticals Germany., H. Mensing Grant/research support from: This study was financially supported by Actelion Pharmaceuticals Germany., K. Kuhr Grant/research support from: This study was financially supported by Actelion Pharmaceuticals Germany., C. Sunderkoetter Grant/research support from: This study was financially supported by Actelion Pharmaceuticals Germany., T. Krieg Grant/research support from: This study was financially supported by Actelion Pharmaceuticals Germany.